Christian spirituality - Pourrat, P. b. (Burns Oates and Washbourne, 1922)
[v.1] From the time of our Lord to the dawn of the Middle Ages --[ v.2] In the Middle Ages -- [v.3-4] Later developments, pt.1 : from the Renaissance to Jansenism.